Coupled electrothermal two-dimensional model for lightning strike prediction and thermal modeling using the TLM method - Elkalsh, Ahmed; Sewell, Phillip; Benson, Trevor M.; Vukovic, Ana (Institute of Electrical and Electronics Engineers, 2017)
This paper presents a fully coupled two-dimensional (2-D) multiphysics model for predicting the location of the arc discharge and lightning channel, and modeling its thermal and electrical behavior as a highly conductive plasma channel. The model makes no assumptions on the physical location of the lightning channel but predicts its appearance purely from the electromagnetic (EM) field conditions. A heat diffusion model is combined with the time-varying nature of the EM problem where material properties switch from linear air material to a dispersive and nonlinear plasma channel. This multiphysics model is checked for self-consistency, stability, accuracy, and convergence on a canonical case where an arc channel is established between two metal electrodes upon exposure to an intensive electric field. The model is then applied to the 2-D study of a diverter strip for aircraft lightning protection.